Boid Inclusion Body Disease Is Also a Disease of Wild Boa Constrictors - Alejandro Alfaro-Alarcón; Udo Hetzel; Teemu Smura; Francesca Baggio; Juan Alberto Morales; Anja Kipar; Jussi Hepojoki (Microbiology Spectrum, 2022)
ABSTRACT Reptarenaviruses cause boid inclusion body disease (BIBD), a potentially fatal disease, occurring in captive constrictor snakes boas and pythons worldwide. Classical BIBD, characterized by the formation of pathognomonic cytoplasmic inclusion bodies (IBs), occurs mainly in boas, whereas in pythons, for example, reptarenavirus infection most often manifests as central nervous system signs with limited IB formation. The natural hosts of reptarenaviruses are unknown, although free-ranging/wild constrictor snakes are among the suspects. Here, we report BIBD with reptarenavirus infection in indigenous captive and wild boid snakes in Costa Rica using histology, immunohistology, transmission electron microscopy, and next-generation sequencing (NGS). The snakes studied represented diagnostic postmortem cases of captive and wild-caught snakes since 1989. The results from NGS on archival paraffin blocks confirm that reptarenaviruses were already present in wild boa constrictors in Costa Rica in the 1980s. Continuous sequences that were de novo assembled from the low-quality RNA obtained from paraffin-embedded tissue allowed the identification of a distinct pair of reptarenavirus S and L segments in all studied animals; in most cases, reference assembly could recover almost complete segments. Sampling of three prospective cases in 2018 allowed an examination of fresh blood or tissues and resulted in the identification of additional reptarenavirus segments and hartmanivirus coinfection. Our results show that BIBD is not only a disease of captive snakes but also occurs in indigenous wild constrictor snakes in Costa Rica, suggesting boa constrictors to play a role in natural reptarenavirus circulation. IMPORTANCE The literature describes cases of boid inclusion body disease (BIBD) in captive snakes since the 1970s, and in the 2010s, others and ourselves identified reptarenaviruses as the causative agent. BIBD affects captive snakes globally, but the origin and the natural host of reptarenaviruses remain unknown. In this report, we show BIBD and reptarenavirus infections in two native Costa Rican constrictor snake species, and by studying archival samples, we show that both the viruses and the disease have been present in free-ranging/wild snakes in Costa Rica at least since the 1980s. The diagnosis of BIBD in wild boa constrictors suggests that this species plays a role in the circulation of reptarenaviruses. Additional sample collection and analysis would help to clarify this role further and the possibility of, e.g., vector transmission from an arthropod host.